Titanium Dioxide Microscale and Macroscale Structures: A Mini-Review - Vu Khac Hoang Bui; Vinh Van Tran; Ju-Young Moon; Duckshin Park; Young-Chul Lee (Nanomaterials, 2020)
Titanium dioxide nanoparticles (TiO2 NPs) have some limitations, such as their low surface area, high bandgap energy, and low recycling ability. To overcome these limitations, TiO2 can be prepared in microscale/macroscale structures. TiO2 microscale structures, in comparison with TiO2 nanopowder, have higher surface areas, more tunable pore structures, and better top photocatalytic activity. In contrast, for TiO2 macroscale structures, although the surface area is lower than TiO2 nanopowder in many cases, they still achieve similar or better photocatalytic performance due to their unique properties. Moreover, both TiO2 microscale and macroscale structures can be easily recovered from reaction media. The difference between these two types of TiO2 structures is a function not only of size but also of the preparation process. Every type of TiO2 structure has its own advantages and disadvantages, as will be discussed further in the following pages. Future perspectives on this research field also will be discussed.